The Interaction of Activity Travel Participation, Built Environment and Social Intensity on Social Health - Rosman, Muhammad Harith Shah (Universiti Teknologi PETRONAS, 2020)
Transportation plays an important role as the mediator for individuals to travel from one destination to another destination in order to perform certain activities throughout the day. It is because every each of us has variety of needs to be fulfilled and the needs only can be achieved if nothing impediment or obstruction distort the urge to perform the activity along the way. Hence, it can be concluded that the human activity-travel behavior is complex, which is it varies according to the socio-demographic and built environment manners of that particular place. Therefore, the decision making of activity travel for individual is irrelevant anymore by following the conventional method, which by assuming all individuals have the similar daily travel and activity pattern. As example, the Trip Analysis has failed to address and relate the interdependencies among the trips and activities recorded and also with temporal constraints on activity scheduling.